Analisis Minat Masyarakat Muslim Menjadi Nasabah Bank Syariah di Masa Pandemi Covid-19 - Eri Romadhon; Supaijo Supaijo (Universitas Galuh, 2023)
The development of Islamic banking in Indonesia during the Covid-19 pandemic was in the spotlight because this condition could be used to introduce the existence of Islamic banks in controlling the economy in Indonesia. The existence of Islamic Banks will continue if the interest of the Muslim community to use Islamic Bank products also increases. The problem of this research is how is the interest of Muslim communities to become customers of Islamic banks during the Covid-19 pandemic. This study uses qualitative data in the form of published data on Islamic Bank monthly financial reports for the period January-July 2020 because during this period the Covid-19 pandemic took place in the form of data on third-party funds, debt financing, and equity financing. The results of the study show that if Islamic banks have the advantage of stability in the concept of equity financing, which means that if it is socialized more among Muslim communities in Indonesia, their interest in using Islamic banks will increase.